A new Grahamella: Grahamella Brumpti n. sp. - Ribeyro, Ramón E. (1918)
Brumpt created in 1911 for certain Gender Grahamella bacillary aspect bodies found in the interior of red blood cells and some animals were observed and described for the first time in 1905 by GRAHAM SMITH  in blood moles (Talpae) captured in Cambridge (England). Later these bodies have been observed and studied by Thomson and Balfour in 1906, by FRANCA and Brumpt in 1911, by Leger Prowazek, HENRY, JOYEUX and VISENTINI  in 1913 by Laveran and MARULLAZ, Scott Macfie, DUDTSCHENKO and COLES in 1914, by Carini  in 1915 and YAKIMOFF in 1917.